2015
DOI: 10.3892/mmr.2015.4413
|View full text |Cite
|
Sign up to set email alerts
|

OSSC1E-K19, a novel phytochemical component of Osteomeles schwerinae, prevents glycated albumin-induced retinal vascular injury in rats

Abstract: In the pathophysiology of diabetic retinopathy (DR), advanced glycation end products (AGEs) and vascular endothelial growth factor (VEGF) are thought to have important roles. It is known that VEGF causes a breakdown of the blood-retinal barrier (BRB) and retinal neovascularization; however, how AGEs affect the retina has largely remained elusive. OSSC1E-K19 is a novel phytochemical component of Osteomeles schwerinae. The objective of the present study was to evaluate the protective effects of OSSC1E-K19 on ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Another novel compound from OSSCE, 4-hydroxy-3′,5′-dimethoxybiphenyl-(1,1′-biphenyl)-3-O-β-D-glucopyranoside (referred to as K19), inhibits the nonenzymatic formation of AGE and the cross-linking of AGE to collagen in vitro. An intravitreal injection of K19 into the AGE-modified rat serum albumin (AGE-RSA)-injected Sprague-Dawley (SD) rats inhibited a retinal vascular leakage by suppressing the expression of vascular endothelial growth factor (VEGF) and by preventing the loss of occludin, an important tight junction protein [19]. We have previously reported that OSSCE reduces the AGE/RAGE binding interaction and the expression of TGF-β1 by pERK1/2, p38MAPK, and IκB phosphorylation in mouse glomerular mesangial cells under diabetic conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Another novel compound from OSSCE, 4-hydroxy-3′,5′-dimethoxybiphenyl-(1,1′-biphenyl)-3-O-β-D-glucopyranoside (referred to as K19), inhibits the nonenzymatic formation of AGE and the cross-linking of AGE to collagen in vitro. An intravitreal injection of K19 into the AGE-modified rat serum albumin (AGE-RSA)-injected Sprague-Dawley (SD) rats inhibited a retinal vascular leakage by suppressing the expression of vascular endothelial growth factor (VEGF) and by preventing the loss of occludin, an important tight junction protein [19]. We have previously reported that OSSCE reduces the AGE/RAGE binding interaction and the expression of TGF-β1 by pERK1/2, p38MAPK, and IκB phosphorylation in mouse glomerular mesangial cells under diabetic conditions [20].…”
Section: Introductionmentioning
confidence: 99%